Comparison of quantitative conformer analyses by nuclear magnetic resonance and Raman optical activity spectra for model dipeptides - Budesínský, Milos; Danecek, Petr; Bednárová, Lucie; Kapitán, Josef; Baumruk, Vladimír; Bour, Petr (The journal of physical chemistry. A, 2008)
Interpretation of the Raman optical activity (ROA) of peptides is difficult because of molecular flexibility and interaction with the solvent. Typically, simulations and experiments are compared in terms of a qualitative agreement between the spectra. However, on a series of the Pro-Gly, Gly-Pro, Pro-Ala, and Ala-Pro dipeptides more precise conformer ratios could be obtained with the aid of the density functional computations and numerical decomposition of the spectral shapes. All observed transitions were assigned, and the computed transition frequencies were scaled accordingly. Then the populations predicted by the optical spectroscopy agreed within a few percent with an analysis of the spin-spin coupling constants based on the Karplus equations, which was confirmed also by a comparison of calculated and experimental NMR couplings. The results are supported by molecular dynamics simulations and related to the previous conformational studies of similar molecules.
Keywords: Reproducibility of Results; Spectrum Analysis, Raman; Vibration; dipeptidy; Quantum Theory; reprodukovatelnost výsledků; Computer Simulation; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; kvantová teorie; počítačová simulace; Reference Standards; Dipeptides; referenční standardy; chemické modely; Molecular Conformation; molekulární konformace; vibrace; Models, Chemical; Ramanova spektroskopie